Identification of mutants for qualitative and quantitative traits through induced mutagenesis in sesame (Sesamum indicum L.): Identification of mutants for qualitative and quantitative traits through induced mutagenesis in sesame (Sesamum indicum L.) - G ARIHARASUTHARSAN; C PARAMESWARI; C VANNIARAJAN; E MURUGAN; CHELVI RAMESH (Journal of Oilseeds Research, 2020)
Sesame is the leading oil seed crop. Creation of new genetic variability is prerequisite for any crop improvementprogramme. The white seeded sesame variety VRI 3 was subjected to induced mutation using gamma ray andcombination treatments (300 Gy + 10 mM EMS, 350 Gy + 10 mM EMS and 400 Gy + 10 mM EMS). From M2generation, mutants were identified for multiple capsules per axis, closed capsules, tri leaf, determinate nature, early maturity, clustered flowering, profuse branching, high number of capsules, variation in capsule length and plant height etc. These mutants have to be forwarded to next generation to identify their true genetic behavior for further utilization in the future breeding programmes.